Ginsenoside Rg3 Alleviates Rotenone-induced Lung Injury in Mice by Its Anti-oxidative Properties - Tian, Wang; Daohui, Wang; Pinyuan, Zhang; Jie, He; Bing, Han (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: Acute lung injury is commonly found in patients with insecticide poisoning and the pathogenesis is related to oxidative stress. Ginsenoside Rg3, one of the main constituents of Panax ginseng C.A. Meyer, shows an anti-oxidative activity. The aim of this study was to evaluate whether ginsenoside Rg3 can alleviate lung injury induced by rotenone in mice. Methods: C57BL/6J male mice were divided into five groups (n=11). The mice in ginsenoside Rg3 groups were treated with ginsenoside Rg3 at dose of 5, 10 or 20 mg/kg. Except for the control group, mice were challenged intragastrically with rotenone at dose of 30 mg/kg, once a day for 6 weeks. Subsequently, the lung tissues of mice were collected. The effect of ginsenoside Rg3 on rotenone-induced lung injury was observed by hematoxylin and eosin staining. The oxidative stress in lung tissues were also examined. Results: Rotenone induced substantial hemorrhage, alveolar wall thickness and neutrophils infiltration. These structural damages were attenuated significantly by ginsenoside Rg3 treatment. The lung injury induced by rotenone was associated with oxidative stress in lung tissues of mice. Compared with the control group, rotenone exposure resulted in the increase of malondialdehyde (MDA), the decreases of the activities of superoxide dismutase (SOD), glutathione peroxidase (GHS-Px), and the glutathione (GSH) content. Nevertheless, ginsenoside Rg3 treatment not only reduced MDA production but also increased the activities of SOD, GSH-Px, and the content of GSH in lung tissue of mice. Conclusion: Taken together, this study demonstrated that ginsenoside Rg3 has potential to ameliorate rotenone-induced lung injury and the mechanism of action of ginsenoside Rg3 is mediated by its anti-oxidative properties.